Relationship between single nucleotide polymorphism of NOS2 gene and inheritance of allergic rhinitis in children - Wu, Xionghui; Zhao, Sijun; Huang, Weiqing; Huang, Min; Xie, Jiang; Liu, Guangliang; Chang, Shuting (Frontiers in Genetics, 2023)
Rhinitis is a common disease related to nasal mucosa. Allergic rhinitis (AR) is a common chronic rhinitis. Its high incidence has a negative impact on the quality of life of many people, especially children. Intelligent medical treatment can improve the detection of influencing factors of AR, and detect AR related genes through intelligent devices, thus improving the detection accuracy. However, there are few studies on AR genetics at present, and it is impossible to understand the relationship between single nucleotide polymorphism (SNP) of NOS2 gene and AR genetics in children. Moreover, the correlation analysis of NOS2 gene SNP is also relatively small, which can not effectively analyze the genetic correlation between SNP and children AR. The SNP detection of NOS2 gene is complex and time-consuming. Therefore, through in-depth analysis of the polymorphism of NOS2 gene, this paper studied the protection mechanism and action mechanism of NOS2 gene to AR, so as to provide theoretical and scientific basis for the diagnosis of children AR. The study found that the concentration of specific IgE (Immunoglobulin E) in rs2297516 of children group was 0.24IU/mL different from that of healthy children group. The specific IgE concentration in rs3794766 of the patient children group was 0.36IU/mL higher than that of the healthy children group. The difference of specific IgE concentration in rs7406657 between the patient children group and the healthy children group was 0.03IU/mL. The total serum IgE concentrations of these three gene sequences were lower in healthy children than in patients. rs3794766 has the smallest change, followed by rs2297516 and rs7406657. This shows that rs7406657 has the highest genetic correlation with AR patients, while rs2297516 has a general genetic correlation with AR patients. The genetic correlation between rs3794766 and AR patients is the smallest. The SNP loci of the three groups are higher in the healthy children group than in the patient children group, which indicates that AR reduces the gene frequency of the three loci. The decrease of gene frequency also increases the susceptibility of children to AR,because the frequency of gene occurrence affects the gene sequence. In a word, intelligent medicine